1964
DOI: 10.1136/jcp.17.4.427
|View full text |Cite
|
Sign up to set email alerts
|

Pathological findings in homocystinuria

Abstract: Pathological findings are described in four cases of a new aminoaciduria in which homocystine is excreted in the urine. All the patients were mentally retarded children. Three of them presented diagnostic features of Marfan's syndrome. Necropsy on one case and biopsy findings in the others are described. Fatty change occurs in the liver. The most striking lesions are vascular. Metachromatic medial degeneration of the aorta and of the elastic arteries in the necropsied case are considered in relation to Marfan'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
2
3

Year Published

1968
1968
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(77 citation statements)
references
References 17 publications
2
70
2
3
Order By: Relevance
“…Fatty infiltration was observed in the liver in all cases examined [10]. MUDD et al [16] demonstrated that Homocystinuria was discovered by FIELD et al [4] in there was a deficiency of cystathionine synthetase Northern Ireland and by GERRITSEN et al [8] in the (4.2.1.13) activity in the liver of a typical case who was United States of America.…”
Section: Introductionmentioning
confidence: 97%
“…Fatty infiltration was observed in the liver in all cases examined [10]. MUDD et al [16] demonstrated that Homocystinuria was discovered by FIELD et al [4] in there was a deficiency of cystathionine synthetase Northern Ireland and by GERRITSEN et al [8] in the (4.2.1.13) activity in the liver of a typical case who was United States of America.…”
Section: Introductionmentioning
confidence: 97%
“…There are at least two lines ofevidence which suggest that excessive homocystine may be associated with atherosclerotic coronary artery disease. First, patients with untreated homocystinuria have a greatly increased tendency to develop severe atherosclerosis and intravascular thromboembolism (1,2). A second line of evidence is the experimental production of preatherosclerotic and atherosclerotic lesions in baboons by a continuous infusion ofhomocystine (3).…”
Section: Introductionmentioning
confidence: 99%
“…Several factors may impede effective homocysteine metabolism. Genetic factors, such as homozygosity for cystathionine-␤ -synthase (CBS 1 ; EC 4.2.1.22) deficiency or 5,10-methylenetetrahydrofolate reductase (MTHFR; EC 1.7.99.5) deficiency, may result in severe hyperhomocyst(e)inemia 2 with serious clinical sequelae, e.g., advanced atherosclerosis of major arteries and/or vascular thrombosis at an early age (9)(10)(11). Milder impairment of enzymes involved in homocysteine metabolism is associated with an increased risk for neural tube defect pregnancies (12) and premature vascular diseases (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%